Partial Purification and Characterization of Urinary Procoagulant - Aoki, N; von Kaulla, K. N (Thrombosis and Haemostasis, 1971)
Partial purification of the human urinary procoagulant was achieved and some of its properties characterized. Purification was accomplished by adsorption of urine with BaSO4, citrate elution, isoelectric precipitation followed by (NH4)2SO4 precipitation and chromatography on hydroxylapatite and Sephadex G-200. Sucrose gradient ultracentrifugation yielded two active components with different sedimentation rates. On electrophoresis the heavier component did not enter the polyacrylamide gel, and the smaller one gave no precipitin band with antihuman serum on immunodiffusion, indicating that the procoagulant does not originate from blood. The purified procoagulant required phospholipids or platelets to activate prothrombin in the presence of coagulation factors V, VII, X and Ca++, while the crude procoagulant preparations activated prothrombin to some extent without an addition of phospholipids or platelets. Thus, the purified urinary procoagulant does not act as a typical tissue thromboplastin whereas the crude preparation may contain it as a component or contaminant. Phosphorus-containing material which may be part of a moiety endowing crude procoagulant with tissue thromboplastin-like activity is largely removed by the purification procedure resulting in low levels in the purified procoagulant.The possible identity (relationship ? ) of urinary procoagulant with the protein component of tissue thromboplastin is discussed.